Ethics of relational and representational disclosures in qualitative migration research. (26th June 2020) - Bell, Justyna; Trąbka, Agnieszka; Pustulka, Paula
Abstract : Purpose: This article engages with the framework of performativity to unpack ethical challenges of interviewing migrants in the setting of shared ethnic background of researchers and participants. From a temporal perspective of shifting contexts from a shared space of the research process, to the post-research reciprocity management, it focusses on the particular aspect of disclosure. Design/methodology/approach: Drawing on several qualitative studies performed by the authors as Polish migrant researchers with Polish migrant communities in Norway, Germany and the United Kingdom, the article documents the ethical challenges that come from a shifting "audience" of the research performance. Findings: Specifically, it discusses how the researchers perform their roles in the field with the focus on rapport building (relational disclosure), to then addressing how this performance changes when the dissemination of findings (representational disclosure) begins and continues over time. Practical implications: This article contributes to the long-standing anthropological debate on self-reflection in the field. Also, demythologizing the relations between a researcher and participants, as well as cautioning research by reporting difficulties at different stages of the research process, will likely make it easier for future researchers who may now be better prepared and anticipate the complexities of doing fieldwork. From a temporal perspective, it can also help a broader scientific community avoid pitfalls from presenting unfavourable results prematurely. Thus, the authors hope that this paper may sensitize migration scholars to the possible predicaments in the process of interviewing their co-ethnics. Originality/value: A methodological innovation lies in a clear focus on the cluster of ethical disclosure dilemmas and the article contributes to a lively debate on ethics of "insider research" in migration studies.